Pengaruh ROA, CR, ATO, dan DER terhadap Return Saham Perusahaan Sub Sektor Aneka Industri Otomotif & Komponen Selama Pandemi Covid-19 - Yudika Alfian; Novi Permata Indah (MES Bogor, 2023)
The automotive and component industry sub-sector is one of the industries that has an impact on the occurrence of the Covid-19 pandemic because there is no mass mobility so that the demand for automotive vehicles has decreased. This study aims to analyze the effect of ROA, CR, TATO, and DER on stock returns in companies in the automotive and component industry subsectors during the Covid-19 pandemic. The research method used in descriptive verification. The results showed that partially TATO had a significant negative effect, while ROA, CR, and DER partially had no significant effect on Stock Return.. ROA, CR, TATO, and DER have a simultaneous effect on Stock Return. Based on the regression model obtained, the diversity of the effects of ROA, CR, TATO, and DER on stucks return is 6% Keywords: Return On Asset; Current Ratio; Total Asset Turnover; Debt to Equity Ratio; Return Shares.